The transport logistics at the enterprise: the methodology and the conception of use - Fedoseev, Vladislav; Shyshkin, Viktor (Management and Entrepreneurship: Trends of Development, 2017)
Recently the actuality of the problem of the transport logistics system effective functioning at the enterprise is, on the whole, caused by several circumstances. In the first place, the transport logistics system is one of the main subsystems of the enterprises’functioning. In other words, it has direct influence on the production activities efficiency, the prime cost, the fulfillment of the order terms. Secondly, the finance sources formation for the enterprise’s activities has recently been taking place at the open capital markets, which have strict selection conditions, and therefore the enterprises have to constantly confirm the effectiveness of their own activities. Thirdly, the external environment priorities change causes the adequate response of the enterprises and the increase of the efforts, aimed to raise the efficiency of every business process, including the transport logistics processes. So, today the main ways of the enterprises’ efficiency increasing are the labor productivity improving, the professional growth of the employees, the management costs reducing and successfull applying the transport logistics functions as well. Purpose. The subject of the study is the economic relations developed in the process of the transport logistics at the enterprise. The purpose of the paper is to determine the essence of the transport logistics, its features and to suggest scientific-grounded proposals for the transport logistics system improving at the enterprises. Design/methodology/approach. The basic principles of this research are the causality and objectivity principles, systematic and comparative methods, institutional and structural-functional approach. Findings. In this article the essence of the transport logistics and its features are described. The possible ways of the logistics activity estimations are determined. Also the ways of the transport logistics system optimization at the enterprises is suggested. According to the proposals in the article the one of the optimization ways is the implementation of the conception «Just in Time». In conformity with it the enterprise can get the following advantages: The material stocks reduce in the production process. The production space sizes reduce and production time shortness. The product quality improve, the quantity of the deficiencies reduce and the logistics service optimization. The rate of enterprise adaptability to the changing requirements of the market increase. The significant acceleration of the transport operations and the efficiency of the transport logistics increase. So, according to the stated advantages, the enterprise can reach the stock level reduction, the high quality standards, the flexibility of the business activity, the production and transportation time reduction, the productivity and efficiency of the enterprise increase. Research limitations/implications. The scientific significance of the article consists in the research of the features of the transport logistics functioning at the domestic enterprises. Originality/value. The suggested in this article measures will further the increase of the Ukrainian enterprises’ competitiveness and will multiply their financial results. The transport logistics optimization, considering as one of the basic element of the enterprise’s activity, will secure the uninterrupted, mutually agreed and effective activity of the enterprises